Tuhan, politik & seks - Hussien Alattas, Syed. ([Gombak, Kuala Lumpur] : JB News Media Network, 2010)
Contemporary issues on political conditions and sexual behavior of the politicians in Malaysia.
In Malay.
Keywords: Anwar Ibrahim, -- Dato' Seri, -- 1947-; Politicians -- Malaysia; Malaysia -- Politics and government